Ternary derivations of triangular algebras - Vandeyar, Morgan (Department of Mathematics and Applied Mathematics, 2022)
Ternary derivations extend the concept of derivations to triples of linear maps. In this thesis, we describe ternary derivations of triangular algebras. We use category theory to approach our study of ternary derivations, while also offering some straightforward computational proofs. Furthermore, we investigate some related maps, called ternary automorphisms and generalised derivations, an intermediary between derivations and ternary derivations. Finally, we suggest areas for further research into different flavours of ternary derivations, such as ternary Lie and Jordan derivations.